2000
DOI: 10.1055/s-2000-7738
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of substance P are decreased in patients with type 1 diabetes

Abstract: Morphological and immunohistochemical studies in diabetic subjects have shown a depletion of the neuropeptide substance P (SP) in the central and peripheral nervous system. This is the first study investigating serum levels of substance P in type 1 diabetes patients (n=50) and controls (n=75) by means of an enzyme immunoassay. The serum level of SP was significantly decreased in the diabetic group compared to the control group (10.12+/-0.29 vs. 12.25+/-0.38 pg/ml; p<0.0001). In diabetic patients, there was no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…This concentration was in the range of the reported SP levels in human serum. [10][11][12] The SP level was the same as that obtained at 50-times dilution. This shows that SP bound to serum proteins was almost fully dissociated.…”
Section: Effect Of Human Serum Albumin (Hsa) and Serum Dilutionmentioning
confidence: 72%
“…This concentration was in the range of the reported SP levels in human serum. [10][11][12] The SP level was the same as that obtained at 50-times dilution. This shows that SP bound to serum proteins was almost fully dissociated.…”
Section: Effect Of Human Serum Albumin (Hsa) and Serum Dilutionmentioning
confidence: 72%
“…Morphological and immunohistochemical studies in type 1 diabetic subjects have shown a depletion of SP in the central and peripheral nervous system, especially in those with diabetic neuropathy [107]. Also, the number of SP-positive fibers are decreased in the dermis of diabetic patients with diabetic neuropathy [108].…”
Section: Alteration Of Substance P In Diabetesmentioning
confidence: 99%
“…The most common complications of delayed wound healing of diabetics are: reduction in chemotactic and phagocytic activities of neutrophils [1], decreased vasculogenesis [2], decreased endothelial nitric oxide synthase (eNOS) activity [3] and reduction of substance P (SP) level [4]. Abnormal nerve distribution and neuroinflammation are also connected with the chronic nonhealing wounds in DM.…”
Section: Introductionmentioning
confidence: 99%